Interleukin-6 is dispensable in pituitary normal development and homeostasis but needed for pituitary stem cell activation following local injury - Laporte, Emma; De Vriendt, Silke; Hoekx, Julie; Vankelecom, Hugo (Frontiers in Endocrinology, 2022)
Recently, we discovered that the cytokine interleukin-6 (IL-6) acts as a pituitary stem cell-activating factor, both when administered in vivo and when added to stem cell organoid cultures in vitro. Moreover, its expression, predominantly localized in the gland’s stem and mesenchymal cells, promptly increases following damage in the adult pituitary, leading to stem-cell proliferative activation. Given these findings that IL-6 is involved in pituitary stem cell regulation, we addressed the question whether the cytokine has an impact on the pituitary phenotype during active phases of the gland’s remodeling, in particular embryonic development and neonatal maturation, as well as during homeostasis at adulthood and aging, all unknown today. Using the IL-6 knock-out (KO) mouse model, we show that IL-6 is dispensable for pituitary embryonic and neonatal endocrine cell development, as well as for hormonal cell homeostasis in adult and aging glands. The findings match the absence of effects on the stem cell compartment at these stages. However, using this IL-6 KO model, we found that IL-6 is needed for the acute stem-cell proliferative activation reaction upon pituitary injury. Intriguingly, regeneration still occurs which may be due to compensatory behavior by other cytokines which are upregulated in the damaged IL-6 KO pituitary, although at lower but prolonged levels, which may lead to a delayed (and less forceful) stem cell response. Taken together, our study revealed that IL-6 is dispensable for normal pituitary development and homeostasis but plays a key role in the prompt stem cell activation upon local damage, although its presence is not essentially needed for the final regenerative realization.